2022
DOI: 10.12737/1842130
|View full text |Cite
|
Sign up to set email alerts
|

University doctoral student: dissertation, preparation for defense, personal organization

Abstract: The practical manual discusses the content, system and technologies of training in doctoral studies of higher educational institutions. Special attention is paid to the distinctive features of the dissertation for the degree of Doctor of Sciences and the analysis of the requirements for a doctoral dissertation. The issues of methodology of scientific creativity at the level corresponding to the doctoral dissertation are highlighted, recommendations on writing, design and defense of the dissertation are present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 0 publications
2
27
1
Order By: Relevance
“…This is consistent with the conclusion of a recent systematic review that social relationships play a central role in predicting teachers’ well-being, which consequently influences their teaching quality ( Hascher and Waber, 2021 ). These results also support the research of Greenway (2017) , who shows that a well-maintained school environment improves students’ achievement on standardized tests and is linked to increased teacher commitment.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This is consistent with the conclusion of a recent systematic review that social relationships play a central role in predicting teachers’ well-being, which consequently influences their teaching quality ( Hascher and Waber, 2021 ). These results also support the research of Greenway (2017) , who shows that a well-maintained school environment improves students’ achievement on standardized tests and is linked to increased teacher commitment.…”
Section: Discussionsupporting
confidence: 88%
“…When students are excited at learning a new skill, they can experience negative emotions about mistakes and situations when they are misunderstood. Thus, operatively provided feedback from a teacher can foster positive emotions in the classroom and serve as a premise for motivation to learn ( Greenway, 2017 ). Lithuanian teachers also emphasized the role of fundamental values (respect, dignity, and kindness) and the importance of collaboration with colleagues by relating it to using empathy at work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyethylene-oxide (PEO) is another polymer-additive, which shows shear-thinning behavior when involved large molecular weight, 80 whose potential to improve jet-stability in water-jet machining has been explored since 1970’s. R. Szymani 81,82 demonstrated the addition of small concentrations of PEO (Polyox-WSR- 301). It significantly improved cutting performance of a high-velocity water-jet in cutting corrugated-boards and wood.…”
Section: Additivesmentioning
confidence: 99%
“…The study also found that counsellors exposed to incidents of suicide had a lower sense of professional self-efficacy (Christianson & Everall, 2008; Lund et al, 2018). Carpenter (2018) pointed out that school counsellors who themselves experienced personal trauma and loss may be even more vulnerable when dealing with adolescents’ suicide attempts. Studies also found that counsellors lack professional training and need the support of a team of suicide prevention professionals (Christianson & Everall, 2008, 2009; Cureton, & Clemens, 2015; Robinson et al, 2013).…”
Section: Review Of Literaturementioning
confidence: 99%